Diabetes during Labour: Types, Mode of Delivery and Fetal Outcome in Erbil Maternity Teaching Hospital - Alaf, Shahla Karim (Sulaimani Journal for Pure and Applied Sciences, 2008)
A field study on 54 pregnant women during labor with pre gestational and gestational diabetes in Erbil Maternity Teaching Hospital ,Erbil city , Kurdistan region Iraq from 1st of January to the 1st of March 2005 was carried out to determine the types of diabetes, mode of delivery and neonatal out come . Total deliveries in this period were 2891, making the rate of diabetes during labor 1.9%. Mean maternal age was33.65±5.35 years, mean maternal weight was 79.50±13.5 kg, 3.7% of patients were primigraivid while 57.41 % were grandmultiparus.63% of diabetic patients in our study were Gestational diabetes while 37% were pregestational diabetes (Type 1 and Type 2 Diabetes).There was no statistically significant correlations between the types of diabetes and maternal age, weight, and parity.61.1% of the patients delivered by Caesarean Section (Emergency and Elective) while 29.6% of cases delivered spontaneously vaginally .The most common indication for Caesarean Section was Cephalo pelvic Disproportion .The perinatal mortality in the study group was 6 (2 macerated stillbirth, 2 fresh stillbirth and 2 early neonatal deaths), there were 5cases (9.2%) of congenital fetal malformations (4 congenital heart disease and one case of club foot (all were newborns of pregestational diabetic mothers).
Keywords: Gestational diabetes; pregestational diabetes; spontaneous vaginal delivery,cephalopelvic disproportion; perinatal; congenital fetal malformations; congenital heartdisease